Constructing an optimal portfolio using efficient frontier and TOPSIS: a case study from technology industry / Siti Umirah Bakari ... [et al.] - Bakari, Siti Umirah; Samsudin, Nur Aslinda; Ahmad Raya, Nur Athirah; Mohd Amin, Farah Azaliney (UiTM Cawangan Negeri Sembilan, 2021)
Currently, the technology sector is one of the fastest-growing sectors in the Malaysian market, contributing 18.5% of the country’s Gross Domestic Product (GDP) in 2018 and is expected to reach 20% by 2020 (Mangram, 2013). Recently, the stock market all over the world, especially Technology Industry companies faced a major impact during this Covid-19 pandemic season. However, due to the basket of equities available in the local stock market, investors must use certain mathematical techniques or models as a basis to choose a good combination of the stocks to maximize the expected rate of return and minimize the overall risk. Hence, diversification helps in protecting investors against the downside in case a particular asset underperforms (Koumou, 2020). Previously, various diversification approaches have been developed to determine the optimum weightage in a portfolio to achieve the most significant possible return with the least risk associated. One of the basic concepts of Modern Portfolio Theory (MPT) is Mean-Variance (MV) optimization that was introduced by Harry Markowitz in 1952. MV is a quantitative tool that allows investors to incorporate their preferences by considering the trade-off between the risk and the expected return. The drawback of MV analysis is mainly related to extreme weights that often occur when the sample efficient portfolio comprises a high number of individual stocks (Merton, 1980). Initially, this study will apply Efficient Frontier, a graphical representation of all possible combinations of risky securities for an optimal level of return given a particular level of risk (Markowitz, 1952). A good stock can also be reflected by the performance of respective companies using financial ratios. The right company selection can reduce the influence of firm-specific risk which in turn can maximize the expected return and minimize the portfolio risk (Mohammed Fauzi et aL, 2019). Therefore, a proper tool to select a company with the best financial performance is significantly important. Additionally, this study also motivated to employ the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) as an alternative to find the optimal weightage of selected stocks before generating an optimal portfolio (Hwang &, Yoon, 1981).